1987
DOI: 10.1038/bjc.1987.223
|View full text |Cite
|
Sign up to set email alerts
|

Stearic acid and carcinogenesis

Abstract: Summary Decreased membrane rigidity is one of the characteristics of malignant cells, resulting in part from the desaturation of stearic acid into oleic acid. In this study we investigated the influence of stearic acid on tumour cell inhibition in vitro and tumour development in vivo. Stearic acid inhibited the colony-forming ability of 4 out of 5 rat and two human tumour continuous cell lines in vitro. In contrast, the colony-forming ability of rat fibroblasts was not inhibited and that of human foetal lung f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 14 publications
2
54
0
Order By: Relevance
“…Stearic acid has already been found to act directly by inhibiting the proliferation of human tumors cells in vitro. 39,40 Most oleic acid in human body is derived from the saturated stearic acid by desaturation of this latter by the enzyme delta 9 desaturase (⌬9-d). Overexpression of this enzyme and consequently high levels of oleic acid has been shown to be required for tumor development in experimental animal studies.…”
Section: Discussionmentioning
confidence: 99%
“…Stearic acid has already been found to act directly by inhibiting the proliferation of human tumors cells in vitro. 39,40 Most oleic acid in human body is derived from the saturated stearic acid by desaturation of this latter by the enzyme delta 9 desaturase (⌬9-d). Overexpression of this enzyme and consequently high levels of oleic acid has been shown to be required for tumor development in experimental animal studies.…”
Section: Discussionmentioning
confidence: 99%
“…When compared with a control diet, a diet containing 14% stearic acid reduced the yield and prolonged the latency of spontaneously developing mammary carcinomas in strain A/ St mice (Bennett, 1984). Both injected stearic acid and an iodinated analogue, iodostearic acid, were also shown to inhibit nitrosomethylurea-induced mammary carcinogenesis in rats, and using in vitro clonogenic assay malignant cells were selectively inhibited (Habib et al, 1987). Stearic acid inhibited the growth of mouse LM cells in vitro (Doi et al, 1978), and the growth of neoplastic rat mammary epithelial cells was inhibited by stearic acid whereas monounsaturated fatty acids such as oleic acid and polyunsaturated fatty acids promoted growth in vitro (Wicha et al, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…When individual fatty acids were investigated, linoleate and oleate increased the growth of nitrosomethylureainduced mammary tumour in vivo (Chan et al, 1983). By contrast, stearic acid inhibited mammary tumour cells in vitro (Doi et al, 1978;Wicha et al, 1979) and also in vivo (Bennett, 1984;Habib et al, 1987). Stearic acid may inhibit cancer cell growth by increasing the cellular stearic:oleic acid ratio and hence the balance of saturated and unsaturated fatty acids in the tissues.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a 17% stearate diet/ 3% safflower oil diet was shown to decrease tumor size in animals injected with MDA-MB-435 cells into the mammary fat pad [46]. When Habib et al injected stearate into NMU treated animals, they observed a decreased number of tumors, decreased latency period until first tumor development, and decreased tumor size [47]. These studies indicate that in addition to dietary modification, it may be possible to alter fatty acid concentrations in patient through injections of individual fatty acids.…”
Section: Primary Tumor Studiesmentioning
confidence: 99%